Analysis of Public Policy as Catalyst for Entrepreneurship Growth and Innovation - Desembrianita, Eva; Zahruddin, Achmad; Arifin, Zainal (West Science Journal Economic and Entrepreneurship, 2023)
This research investigates the role of public policy as a catalyst for entrepreneurship growth and innovation in Bandung City. Through a mixed-methods approach comprising qualitative interviews and quantitative surveys, this study explores the impact of policies on the entrepreneurial ecosystem. Qualitative findings reveal themes of policy awareness, effectiveness, collaboration, funding access, and educational support. Quantitative analysis corroborates these themes, highlighting variations in policy perceptions, impacts, and innovation outcomes. The discussion interprets these findings within established theoretical frameworks, offering insights for policymakers and stakeholders aiming to enhance the city's entrepreneurial landscape.